2021
DOI: 10.1177/1081286521997511
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and analysis of a magnetoelastic annular membrane placed in an azimuthal magnetic field

Abstract: This work presents the development of a 2D nonlinear magnetoelastic framework for a thin membrane undergoing large deformations. An asymptotic [Formula: see text] theory is obtained, starting from the 3D variational magnetostatic and force balance equations for a weakly magnetizable material, using the approach described by Steigmann. The model is subsequently specialized to axisymmetry and applied to a pre-stretched annular membrane deforming under azimuthal magnetic field and transverse pressure loading. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In what follows, an asymptotic 2D theory for an electro-magneto-elastic membrane is derived starting from the 3D governing equations. The methodology used here is analogous to the work presented in Ali et al (2021).…”
Section: Variational Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…In what follows, an asymptotic 2D theory for an electro-magneto-elastic membrane is derived starting from the 3D governing equations. The methodology used here is analogous to the work presented in Ali et al (2021).…”
Section: Variational Formulationmentioning
confidence: 99%
“…2D magnetostatic governing equations of a membrane can be derived starting from the 3D magnetostatic equations (4) and jump conditions (9). Assuming that the magnetic field in free space is axially homogeneous, i.e., b + f = b − f = b f , the governing equations maybe derived as (Ali et al (2021))…”
Section: Magnetostatic Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the ratio of the magnetic constant to the elastic constant defines the deformation mode in the system under study. The work [ 89 ] developed the membrane theory for MAE-based devices. The asymptotic expansion of variational equations of 3D continuum theory was used to obtain an effectively two-dimensional theory of membrane deformation.…”
Section: Main Mae Modeling Approachesmentioning
confidence: 99%
“…Choice of symmetric geometries allowed them to convert the resulting partial differential equations to ordinary differential equations. Ali et al (2021) derived a 2D membrane theory for magnetoelasticity using asymptotic analysis and studied the deformation of an annular membrane. Goulbourne et al (2007) derived the equilibrium equations and studied time-dependent response of a circular inflated electroelastic membrane.…”
Section: Introductionmentioning
confidence: 99%